2014
DOI: 10.1192/bjp.bp.113.129965
|View full text |Cite
|
Sign up to set email alerts
|

Biological vulnerability to depression: linked structural and functional brain network findings

Abstract: This is the first evidence of connected structural and functional DMN abnormalities in recovered-state MDD, supporting recent hypotheses on biological-level vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 39 publications
3
61
2
Order By: Relevance
“…Sheline et al (2010) suggested that this widespread aberrant connectivity likely contributed to the diverse symptomatology of MDD. In contrast to findings from treated subjects with MDD ( Sheline et al, 2010;Nixon et al, 2014), we did not find that this region exhibited a significant increase of functional connectivity with the precuneus by the unconstrained whole-brain search in medication-naïve, first-episode MDD. Nevertheless, we observed that in patients with greater severity of depression this region showed hyperconnectivity with the precuneus, highlighting that the dorsal nexus "hot-wiring" might be related to clinical severity, and indicating vulnerability for recurrences in depression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Sheline et al (2010) suggested that this widespread aberrant connectivity likely contributed to the diverse symptomatology of MDD. In contrast to findings from treated subjects with MDD ( Sheline et al, 2010;Nixon et al, 2014), we did not find that this region exhibited a significant increase of functional connectivity with the precuneus by the unconstrained whole-brain search in medication-naïve, first-episode MDD. Nevertheless, we observed that in patients with greater severity of depression this region showed hyperconnectivity with the precuneus, highlighting that the dorsal nexus "hot-wiring" might be related to clinical severity, and indicating vulnerability for recurrences in depression.…”
Section: Discussioncontrasting
confidence: 99%
“…DMN hyperconnectivity with the dorsal nexus has also been demonstrated in previously depressed but recovered subjects (Nixon et al, 2014) and first degree relatives of depressed subjects (Norbury et al, 2011), but so far not reported in medication-naïve, firstepisode depression. To our knowledge, only two previous studies have examined DMN connectivity in medication-naïve first-episode subjects.…”
Section: Introductionmentioning
confidence: 91%
“…Studies examining the resting state with fMRI demonstrate hyperconnectivity within the DMN in patients with MDD (Greicius et al, 2007), dysthymic disorder , and remitted depression (Nixon et al, 2014). Antidepressants reduce DMN hyperconnectivity in depressed patients to levels comparable with healthy control participants , and reductions in prefrontal connectivity correlate with symptom improvement (Wang et al, 2015).…”
Section: Dmn-dlpfc Connectivitymentioning
confidence: 99%
“…We also found that the gyrification trajectory of patients with MDD might be different from HC, as well as from BD-I and SCZ, but no brain region showed significant alteration of gyrification in MDD. In fact, several studies with small sample size showed higher gyrification in MDD than in healthy controls 57,58 , while some showed lower 18,59 , which could be due to differences in genes or brain connections 57,59 . Further studies will be necessary to clarify these inconsistent results.…”
Section: Discussionmentioning
confidence: 98%